Evaluasi Program Menggunakan Model Participant-Oriented Approach (Fitzpatrick, Sanders, Worthen) - Kalvin Kalvin; Suranto Suranto (Departement of Mathematics Education, 2023)
This literature study design presents scientific ideas regarding the Participant-oriented approach (Fitzpatrick, Sanders, Worden) evaluation model using different case study assignments. The participant oriented approach (Fitzpatrick, Sanders, Worthy is the focus of the author in making scientific articles using a literature study design through research journals that are related to the topic of the article. The author uses three different case studies as comparisons and as information for readers regarding the participant oriented approach by fitzpatrick, sanders, worthen. the three cases include the training program evaluation model, the bloom's mastery learning model outside formal education hours, on weekdays, and on weekends, and the field-based training model program for mental health workers , community workers, psychosocial workers and counselors.